PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN KECAP MANIS ABC DI JABODETABEK - Halimatus Sa’diyah; Rizki Adi Puspita Sari; Elpawati Elpawati (AGRIBUSINESS JOURNAL, 2017)
This study aims to analyze effects of marketing mixes on consumer loyalties. A total of 100 respondents drawn from consumers who never consumed or consumed soy sauce ABC at least once during the last year were interviewed. Descriptive analyses and methods Path Analyses were used to analyze the relationship between the independent variables, namely products, prices, places, and promotions on the dependent variable, customer loyalties (Y2) through mediating variables or intermediate variables, consumer behaviors (Y1). Results indicated that the variables of products, prices, places, and promotions jointly had influences on consumer behaviors while partial test showed that variables of product and promotion had direct effects on consumer loyalties, and variables of price and place did not have any influences directly but through intermediary variables namely consumer behaviors.